Cytomegalovirus (CMV) seroprevalence among women at childbearing age, maternal and congenital CMV infection: policy implications of a descriptive, retrospective, community-based study - Assaf Ben Shoham; Yechiel Schlesinger; Ian Miskin; Ziva Kalderon; Rachel Michaelson-Cohen; Yonit Wiener-Well (BMC, 2023)
Abstract Background Maternal CMV infection during pregnancy, either primary or non-primary, may be associated with fetal infection and long-term sequelae. While guidelines recommend against it, screening for CMV in pregnant women is a prevalent clinical practice in Israel. Our aim is to provide updated, local, clinically relevant, epidemiological information about CMV seroprevalence among women at childbearing age, the incidence of maternal CMV infection during pregnancy and the prevalence of congenital CMV (cCMV), as well as to provide information about the yield of CMV serology testing. Methods We performed a descriptive, retrospective study of women at childbearing age who were members of Clalit Health Services in the district of Jerusalem and had at least one gestation during the study period (2013-2019). We utilized serial serology tests to determine CMV serostatus at baseline and at pre/periconception and identified temporal changes in CMV serostatus. We then conducted a sub-sample analysis integrating inpatient data on newborns of women who gave birth in a single large medical center. cCMV was defined as either positive urine CMV-PCR test in a sample collected during the first 3 weeks of life, neonatal diagnosis of cCMV in the medical records, or prescription of valganciclovir during the neonatal period. Results The study population Included 45,634 women with 84,110 associated gestational events. Initial CMV serostatus was positive in 89% women, with variation across different ethno-socioeconomic subgroups. Based on consecutive serology tests, the detected incidence rate of CMV infection was 2/1000 women follow-up years, among initially seropositive women, and 80/1000 women follow-up years, among initially seronegative women. CMV infection in pregnancy was identified among 0.2% of women who were seropositive at pre/periconception and among 10% of women who were seronegative. In a subsample, which included 31,191 associated gestational events, we identified 54 newborns with cCMV (1.9/1000 live births). The prevalence of cCMV among newborns of women who were seropositive at pre/periconception was lower than among newborns of women who were seronegative (2.1 vs. 7.1/1000). Frequent serology tests among women who were seronegative at pre/periconception detected most primary CMV infections in pregnancy that resulted in cCMV (21/24). However, among women who were seropositive, serology tests prior to birth detected none of the non-primary infections that resulted in cCMV (0/30). Conclusions In this retrospective community-based study among women of childbearing age characterized by multiparity and high seroprevalence of CMV, we find that consecutive CMV serology testing enabled to detect most primary CMV infections in pregnancy that led to cCMV in newborns but failed to detect non-primary CMV infections in pregnancy. Conducting CMV serology tests among seropositive women, despite guidelines' recommendations, has no clinical value, while it is costly and introduces further uncertainties and distress. We thus recommend against routine CMV serology testing among women who were seropositive in a prior serology test. We recommend CMV serology testing prior to pregnancy only among women known to be seronegative or women whose serology status is unknown.